MECHANICAL DAMAGE CAUSED BY SEED METERING SYSTEMS - Almeida, Rogério de Araújo (2007)
Effects of mechanical damage caused by five seed metering systems were evaluated in four crops. Seed samples were collected before and after passing through the measuring systems and submitted to tests of purity, germination and vigor. There was no difference in the level of mechanical damage caused by the metering systems used for maize seeds. For common bean seeds, minor effects were verified when using the vacuum metering disk and the feed cup. The fluted feed system showed the best performance for rice seeds, and the horizontal perforated disk and feed cup systems exhibited the best results for soybean seeds. The vacuum metering disk system caused the highest level of mechanical damage to soybean seeds. KEY-WORDS: Planter machine; seed distributor; fluted feed.